The Role of Quality Improvement Process in Improving the Culture of Information among Health Staff in Ghana - Richard Okyere Boadu; Godwin Adzakpah; Peter Agyei-Baffour (Advances in Public Health)
Background. Over the past decades, knowledge and understanding have grown regarding the role that health information systems play in improving global health. Even so, using data to make evidence-informed decisions is still weak in most low- and middle-income countries. People do not always act on what they are told to do but act on sharing what is important and valued in an organization. Shared principles related to information systems are alluded to as a pre-existing culture of data collection or “culture of information” without specifying how these values originate and sustain themselves. They work in an organizational environment, which ultimately impacts them through organizational directives, principles, and practices. The objective of the study was to determines the role of quality improvement process in improving culture of information among health staff in Ghana, particularly in the Ejisu Juaben Health Service over time. Methods. A quasi-non-experimental pre- and post-intervention study was conducted in 26 health facilities in the Ejisu Juaben municipal health service of Ghana. The study involved assessment of perceived culture of information of staff coupled with training of 141 core staff selected from 26 facilities who were involved in data collection and use of information through application of data quality improvement training module over a twelve-month period. Results. Overall perceived promotion of culture of information improved from 71 percent in the baseline to 81 percent in the endline. Test-retest analysis suggested that the mean levels of the indices measuring promotion of a perceived culture of information, was significantly higher in endline compared to the situation in baseline. Conclusions. The study concluded that the improvement in staff perceived culture of information improved significantly overtime and this might have been contributed by the application and adoption of quality improvement training.